1991
DOI: 10.1017/s0030605300034074
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of large avian frugivores and the management of Neotropical protected areas

Abstract: Large frugivorous forest birds are among the most endangered avian groups in the Neotropics. Despite this fact, there has been little field work on members of these groups or on other large Neotropical forest birds. While current studies of Neotropical forests are beginning to provide data for reserve management at the ecosystem level, we lack information for management of particular species or habitats. Throughout Latin America, large forest frugivores are economically important as food, as pets or in local c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 6 publications
0
27
0
3
Order By: Relevance
“…The model indication that curassows had not been harvested unsustainably should, however, be interpreted with caution. These large cracids can serve as good indicators of hunting pressure (Silva and Strahl 1991;Strahl and Grajal 1991), and the small number of kills recorded can also mean that curassows had already been severely depleted. This is consistent with the fact that hunters rarely bypassed an opportunity to kill a curassow, whereas this was often the case with smaller cracids and other gamebirds.…”
Section: Includes Both Sympatric Congeners Rusty-margined Guan (Penementioning
confidence: 98%
“…The model indication that curassows had not been harvested unsustainably should, however, be interpreted with caution. These large cracids can serve as good indicators of hunting pressure (Silva and Strahl 1991;Strahl and Grajal 1991), and the small number of kills recorded can also mean that curassows had already been severely depleted. This is consistent with the fact that hunters rarely bypassed an opportunity to kill a curassow, whereas this was often the case with smaller cracids and other gamebirds.…”
Section: Includes Both Sympatric Congeners Rusty-margined Guan (Penementioning
confidence: 98%
“…If the frugivores impacted by fruit harvest are seed dispersers, then their reduced abundance and activity may also affect dispersal of seeds (DeSteven and Putz 1984, Strahl and Grajal 1991, Hamann and Curio 1999, Loiselle and Blake 2002. Less time spent in fruiting patches may increase the dispersal of ingested seeds if frugivores are forced to move farther and more frequently in search of food (Pratt and Stiles 1983).…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…In many areas of Latin America cracid populations are declining. Subsistence hunting is an important cause of these declines (Delacour and Amadon, 1973;Thiollay, 1989;Ayres et al, 1991;Silva and Strahl, 1991;Strahl and Grajal, 1991;Vickers, 1991;Collar et al, 1992). Habitat destruction has also been responsible for population declines of several species (Strahl and Grajal, 1991) and for the near extinction of one curassow (Texeira and Snow, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that cracids are not suitable for wild-meat harvests because of their slow rate of population recovery (Lovejoy and Brash, 1984;Terborgh, 1986;Estudillo-Lopez, 1988;Silva and Strahl, 1991;Strahl and Grajal, 1991). Thus, conservation of cracids has focused only on fully protected areas (Estudillo-Lopez, 1988;Strahl and Grajal, 1991). Many cracid populations, however, inhabit areas outside parks and are hunted by rural people to varying degrees.…”
Section: Introductionmentioning
confidence: 99%